Trained librarian - Johnson, Susan Effle (My University, 1896)
Introduction: It is in this age when intellectual growth is so rapid, when hundreds of publishing firms send out thousands of pamphlets, magazines, and books daily that we need the librarians. In the future the work of the librarian will be very different from that of the past. As the world has advanced and the people have become cultured and care more for good reading, the librarians have marched to the front. The libraries of the country have become more numerous and with the increase of the libraries has come the need of more librarians; as the need for more workers becomes greater so, too, is the world calling for better work, hence for those who expect to take up this profession, there is great advantage in being trained for the library or the work of the librarians.
Citation: Johnson, Susan Effle. Trained librarian. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Intellectual growth; Librarian; Publishing firms; Theses; Manuscripts (documents)